2014
DOI: 10.4028/www.scientific.net/ssp.219.115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electrostatic Effects on Wet Etching Phenomenon in Nanoscale Region

Abstract: The microminiaturization of semiconductor devices has made it necessary to control the wet etching process on the nanometer order. It is therefore extremely important to understand wet etching reactions in the nanoscale region of solid-liquid interfaces, in order to assist in optimizing process conditions to satisfy the severe demand for semiconductor devices. Simulations performed to analyze the behavior of liquid molecules in the nanoscale region have been reported [1], but there have been few reports of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…With the continuous scaling of microelectronics devices, the kinetics of wet etching within nanometer-sized three-dimensional spaces create new challenges. Okuyama et al reported that the etching rate in nanometer size spaces was suppressed by the depletion of the HF2 − as etchant ions in the solution and induced by the overlap of the electric double layer (EDL) on opposite surfaces of the nanostructures [1]. However, the thickness of EDL estimated by the Debye length equation [2] is less than 1 nm on the reported system in the etching solution.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous scaling of microelectronics devices, the kinetics of wet etching within nanometer-sized three-dimensional spaces create new challenges. Okuyama et al reported that the etching rate in nanometer size spaces was suppressed by the depletion of the HF2 − as etchant ions in the solution and induced by the overlap of the electric double layer (EDL) on opposite surfaces of the nanostructures [1]. However, the thickness of EDL estimated by the Debye length equation [2] is less than 1 nm on the reported system in the etching solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their corresponding etching reaction kinetics and specificity may vary from those of bulk/plain surfaces or microscale confinements, and the transport of reactants and products of the etching reaction may also affect the reaction. As a result, nonuniform etching rate and different selectivities have been observed when features with different nanoconfinements are present on the same wafer, which cause serious challenges for etching control and thus significantly affect the fabrication yield and quality. , To properly address this challenge, efforts have been made on investigating wet etching reactions in nanoconfinements (WERIN) filled with a variety of materials and several factors that could affect the etching reaction have been proposed. Specifically, Okuyama et al studied diluted hydrofluoric acid (dHF) etching of SiO 2 -filled 2-D planar nanochannels and discovered that the etching length is a linear function of the etching time, suggesting a kinetics-limited reaction . They found that the resulting constant etching rate decreases with decreasing channel height and hypothesized that it is a result of reactant concentration changes due to electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…9−13 Specifically, Okuyama et al studied diluted hydrofluoric acid (dHF) etching of SiO 2 -filled 2-D planar nanochannels and discovered that the etching length is a linear function of the etching time, suggesting a kinetics-limited reaction. 10 They found that the resulting constant etching rate decreases with decreasing channel height and hypothesized that it is a result of reactant concentration changes due to electrostatic interactions. Following their study, Vereecke et al and Ueda et al investigated wet etching of TiNfilled and SiO 2 -filled 1-D/2-D nanoconfinements, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, wet processing in nanoconfined volumes was found not to follow the rates encountered on flat surfaces, but without a clear mechanism proposed. For example, the overlap of surface electrostatic double layers was proposed as an explanation (7), but the high ionic strength of the used solutions excluded this argument (8).…”
Section: Introductionmentioning
confidence: 99%